Hormonal modulation of sex differences in resistance to Leishmania major systemic infections. - Mock, B A (1988)
Differences in susceptibility to intravenously inoculated Leishmania major were observed in male and female mice of the BALB/cAnPt, DBA/2N, and DBA/2J strains and (BALB/cAnPt x DBA/2N)F1 hybrids. In all cases, males had significantly higher liver parasite burdens than females. Orchidectomy of BALB/c males resulted in a 20% decrease in the number of parasites in the liver compared with either normal or sham-gonadectomized controls. Additionally, testosterone treatment of female BALB/c mice resulted in an 88% increase in the number of liver amastigotes. These results suggest that the hormone testosterone can modulate systemic L. major infections in BALB/c mice.